Estudo e otimização da reação de hidratação do hidróxido de cálcio - Silva, Alaine Cardoso (2007)
Slaked lime is a suspension of hydrated lime in water that can contain up to 40% of solids in suspension. It is a cheap base with high alkaline content. It is used in a variety of industrial applications such as process of treatment of water and sewerage, treatment of waste, in the stages of sugar clarification, in gas cleaning systems, among several other processes. The quality of the suspensions of slaked lime depends on the quality of lime used and on a careful choice of the conditions during the hydration process. A high quality slaked lime is a product with a small quantity of insoluble residues, high specific surface area, high alkaline content, small particle size and low viscosity. Therefore, the objective of this work was study the best conditions of temperature, concentration (relation lime/water), lime particle size, and agitation to produce a superior slaked lime. A statistic analysis was performed using the results obtained in order to optimize the operational conditions of the hydration process. It was observed that the use of small lime particle size, a temperature around 74 °C and concentrations between 217 g/L e 228 g/L minimize the amount of insoluble residue. The use of the same particle size and temperature, with a concentration around 175 g/L contributes to increase of the specific surface area of calcium hydroxide. It was observed that the degree of agitation does not interfere in any slaked lime properties investigated. The majority of the slaked lime suspensions presented a pseudoplastic fluid behavior. It was verified that the samples with high reactivity and high surface area presented smaller agglomeration observed by images of scanning electron microscopy. Parametric optimization disclosed the conditions necessary to produce a slaked lime suspension of fine quality.